ANALISIS PERKEMBANGAN GIRO TABUNGAN DAN DEPOSITO DI PT BANK SULUT - Kristin, Prilliana; Roring, Mieke; J. Rogahang, Joula (JURNAL ADMINISTRASI BISNIS, 2016)
Absract, The study is based on the bank’s financial institutions are very strategic role in the economy of the country, to execute its role as an institution that serves the management of financial services to facilitate the efforts of the government program and the community in general. Collecting funds within the bank there are some products that are offered include: Current Accounts, Savings and time deposits. The research problems are: is how the development of demand deposits, savings and time deposits in PT Bank North Sulawesi? and the purpose of the study was to determine the development of demand deposits, savings and time deposits in a few years (the period). The method used in this research is descriptive quantitative method, the data collection techniques of interview, observation and document. Which becomes a variable is the calculation of the amount of demand deposits, savings and time deposits in the last 5 years. Technical analysis of the data using linear trend analysis of time series approach. Results of the analysis showed above trend growth or increased demand deposits, savings deposits from the 2010 s / d in 2014 and forecast forward for the next 3 years of current accounts in 2015 will grow 13,238,058, 2016, 15,053,028, and in 2017 will berjumlah16.867.998 , for savings, 2015, 1269863, 2016 1547591, 2017, 1,825,318. and deposits in 2015, 11,610,185, 2016, 14,871,173, 2017, 18,123,156. Keyworsd : the development of demand deposits, savings and time deposits